2019
DOI: 10.1002/jgm.3065
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNAs in cancer: Another layer of complexity

Abstract: We review the most well characterized long non‐coding RNAs (lncRNAs) with important roles in hallmarks of cancer, additionally including lncRNAs with a higher potential for clinical application. LncRNAs are transcripts larger than 200 nucleotides in length that do not appear to have protein‐coding potential, although some of those may produce small functional peptides. These transcripts have attracted significant attention from researchers as a result of their role in genetic regulation, including epigenetic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 272 publications
(301 reference statements)
0
67
0
1
Order By: Relevance
“…Long noncoding RNAs (LncRNAs) are a class of nonprotein-coding transcripts (larger than 200 bases) that participate in a variety of physiological and pathological functions (Wang et al, 2018). Increasing evidence suggests that lncRNAs play a critical role in cancer cell proliferation, migration, and apoptosis, and irregular lncRNAs levels are associated with malignancy initiation and development (Sun et al, 2018;de Oliveira et al, 2019;Flippot et al, 2019). Unfortunately, it is difficult to clarify lncRNA-lncRNA, lncRNA-miRNA, and lncRNA-protein networks due to the large number of lncRNAs involved in these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (LncRNAs) are a class of nonprotein-coding transcripts (larger than 200 bases) that participate in a variety of physiological and pathological functions (Wang et al, 2018). Increasing evidence suggests that lncRNAs play a critical role in cancer cell proliferation, migration, and apoptosis, and irregular lncRNAs levels are associated with malignancy initiation and development (Sun et al, 2018;de Oliveira et al, 2019;Flippot et al, 2019). Unfortunately, it is difficult to clarify lncRNA-lncRNA, lncRNA-miRNA, and lncRNA-protein networks due to the large number of lncRNAs involved in these processes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of studies have shown the significance of lncRNA in tumor development. With the development of sequencing technology, many new tumor-associated lncRNAs have emerged [11]. Based on their functions in tumor development, lncRNAs could be divided into tumor-promoting factors, tumor-suppressor factors and tumor-promoting/tumor-suppressor factors [18].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidences have revealed the functions of lncRNAs in many biological processes through multiple levels [10]. In particular, differentially expressed lncRNAs participate in tumor development, and can be utilized as diagnostic marker for predicting the risk of tumorigenesis [11,12]. For example, lncAA174084 expression in gastric juice can predict the occurrence of gastric cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, genomic instability, inflammation, reprogramming of energy metabolism, and evading immune destruction were also included [28]. There are many lncRNAs well described associated with cancer [29], and, herein, we highlighted some lncRNAs with strong evidence for cancer process association and with molecular details, for exemple (Figure 1). The influence of those long noncoding RNAs in hallmarks of cancer is due to the regulation of different pathways.…”
Section: Lncrnas Act In Hallmarks Of Cancermentioning
confidence: 97%